VD_FINDINFO Pron / 2010 / 131 vom 1. Dezember 2010 - VD Tribunal cantonal (2010)
MODÉRATION, HONORAIRES, HONORAIRES CALCULÉS EN FONCTION DU RÉSULTAT POSITIF, AVOCAT | 400 CO, 45 al. 1 LPAv, 45 LPAv, 48 LPAv, 50 al. 1 LPAv, 50 al. 3 LPAv, 50 LPAv